Nonlocal fracture analysis of fiber reinforced composites under heat flux loading - Kunyang Cao; Ruchao Gao; Wenzhi Yang; Zhijun Liu; Zengtao Chen (Case Studies in Thermal Engineering)
This work aims to explore the fracture characteristics of fiber reinforced composites under heat flux loadings in the framework of Eringen's nonlocal elasticity. Epoxy-based composites reinforced by T300 graphite fiber, AS graphite fiber and S-Glass fiber are examined to study the temperature and nonlocal thermal stress conditions around the crack tips. Both the horizontal and vertical fibers are considered to make the comparisons. By means of the Fourier transform method, the thermal and elastic problems are converted to the singular integral equations and dual integral equations, respectively. After evaluating the integral equations numerically, the temperature and nonlocal stresses around the crack tips are illustrated graphically. The effects of the fiber volume fractions, fiber orientations, and the nonlocal characteristic lengths are investigated in detail. The application of nonlocal theory is proved to be capable of taking the composite's size effect into account as well as removing the singular stress field near the crack tips, which contributes to the development of the fibrous composite's application in various engineering industries.